2018
DOI: 10.1029/2018gl080158
|View full text |Cite
|
Sign up to set email alerts
|

Global Assessment of Supraglacial Debris‐Cover Extents

Abstract: Rocky debris on glacier surfaces influences ice melt rates and the response of glaciers to climate change. However, scarce data on the extent and evolution of supraglacial debris cover have so far limited its inclusion in regional to global glacier models. Here we present global data sets of supraglacial debris‐cover extents, based on Landsat 8 and Sentinel‐2 optical satellite imagery. We find that about 4.4% (~26,000 km2) of all glacier areas (excluding the Greenland ice sheet and Antarctica) are covered with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
206
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(234 citation statements)
references
References 38 publications
(57 reference statements)
5
206
2
Order By: Relevance
“…The Randolph Glacier Inventory (RGI v6.0;RGI Consortium, 2017) includes 95,536 glaciers over HMA (regions 13, 14, and 15), covering an area of ∼97,605 ± 7,935 km 2 (assuming ∼8% uncertainty; Pfeffer et al, 2014). Approximately 11% of this glacier area and 18% of the corresponding glacier volume is debris-covered (Kraaijenbrink et al, 2017;Scherler et al, 2018). Most glaciers in the central and eastern Himalaya receive ∼80% of their annual accumulation from the summer monsoons (Bookhagen et al, 2005), while glaciers in the western Himalaya and Karakoram receive ∼60-70% from westerly extratropical cyclones (Bolch et al, 2012;Kapnick et al, 2014;Maussion et al, 2014;Cannon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Randolph Glacier Inventory (RGI v6.0;RGI Consortium, 2017) includes 95,536 glaciers over HMA (regions 13, 14, and 15), covering an area of ∼97,605 ± 7,935 km 2 (assuming ∼8% uncertainty; Pfeffer et al, 2014). Approximately 11% of this glacier area and 18% of the corresponding glacier volume is debris-covered (Kraaijenbrink et al, 2017;Scherler et al, 2018). Most glaciers in the central and eastern Himalaya receive ∼80% of their annual accumulation from the summer monsoons (Bookhagen et al, 2005), while glaciers in the western Himalaya and Karakoram receive ∼60-70% from westerly extratropical cyclones (Bolch et al, 2012;Kapnick et al, 2014;Maussion et al, 2014;Cannon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…6f). These results suggest that regional geographic variability of debris cover, that is likely influenced by geological conditions, together with trends in 280 warming and precipitation over the past few decades, influenced the overall distribution of proglacial and supraglacial lake area in their current states across HMA (Haritashya et al, 2018;Scherler et al, 2018;Dan and CLAGUE, 2011;Bo et al, 2019). text are labelled.…”
Section: Influencing Factors Of Current Distribution Of Glacial Lakesmentioning
confidence: 96%
“…The importance of these glaciers for regional water resources via temporarily storing and releasing water at various time scales has long been recognized [1][2][3][4]9]. In particular, the Tibetan Plateau and its surroundings host a large number of debris-covered glaciers [10][11][12][13] on which the ablation zone is extensively covered by supraglacial debris with different thicknesses. It is well known that debris cover can enhance or attenuate ice melt rates compared to bare ice, depending on its thickness [14,15], called the debris-cover effect [13].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of debris cover can largely influence the structure of the glacier's hydrological system and its evolution by controlling melt rate and its spatial pattern [16][17][18][19], with important implications for the catchment runoff [16,18,20]. Note that the extent of supraglacial debris cover is likely to increase with glacier shrinkage [11,21]. Analysis of one basin of the Nepal Himalayas found that the debris-covered ice provides much more meltwater to the total runoff [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation